(untitled) (Agroindustrial Science, 2025)
In Ecuador, bananas are the second most important export product after oil and a key pillar of its economy. However, their production faces phytosanitary challenges, primarily the attack of foliar diseases caused by phytopathogenic fungi, traditionally controlled through the application of chemical fungicides. This study evaluated, under in vitro conditions, the antagonism of three Trichoderma strains (T. harzianum, T. asperellum, and T. sp.) against Neocordana musicola and Phoma musae, pathogens isolated from diseased leaves collected in the province of Santo Domingo de los Tsáchilas, Ecuador. The trials were evaluated using dual cultures, quantifying mycelial growth and the degree of competition for space. A completely randomized design (CRD) with an axb factorial arrangement and two controls was used. Based on the results, the highest percentage of inhibition corresponds to T. harzianum against Neocordana musicola with 97.6% and T. harzianum against Phoma musae with 78.6%, followed by T. asperellum against Neocordana musicola with 76.8% and T. asperellum against Phoma musae with 46.6%. In comparison, T. sp. registered the lowest percentages, being 39.4% against Neocordana musicola and 35%,4 against Phoma musae. These results demonstrate the potential of Trichoderma harzianum as a biological control agent.